THE EFFECTIVENESS OF CIVIC OVERSIGHT IN COMBATING CORRUPTION: THE CASE OF PUBLIC COUNCILS IN UZBEKISTAN (Web of Teachers: Inderscience Research, 2026)
This article evaluates the role and practical effectiveness of civic oversight in combating corruption in the Republic of Uzbekistan, based on the activities of public councils. The study analyzes the legal framework, organizational structure, and actual performance of these councils, and reveals existing opportunities and limitations in establishing oversight over state bodies. The article provides a theoretical and empirical justification of mechanisms aimed at preventing corruption through civil society institutions.